Resolution of Cancer-Promoting Inflammation: A New Approach for Anticancer Therapy - Zhang, Qi; Zhu, Bo; Li, Yongsheng (Frontiers in Immunology, 2017)
Inflammation is a protective response that eliminates harmful stimuli and restores tissue homeostasis, whereas the failure to resolve inflammation leads to the development of malignancies. Immune cells in the tumor inflammatory microenvironment endow cancer cells with their specific hallmarks, including mutations, metabolic reprogramming, angiogenesis, invasion and metastasis. Targeting the inflammatory microenvironment with anti-inflammatory drugs (e.g., aspirin) or by enhancing anti-tumor immunity (e.g., chimeric antigen receptor T cell therapy) has been extensively investigated and has achieved promising results in many cancers. Recently, a novel approach promoting anti-tumor immunity via a dual anti-inflammatory and pro-resolving strategy was proposed based on the discovery of potent, endogenous, specialized pro-resolving mediators (SPM), including lipoxins, resolvins, protectins and maresins. In this review, we describe the updated principal cellular and molecular mechanisms of inflammation resolution and cancer immunity and discuss the pro-resolution strategy in cancer treatment and prevention.